The Parameters Affect on Power Coefficient Vertical Axis Wind Turbine - Qasim, Ahmed Y.; Usubamatov, Ryspek; Zain, Zuraidah M.; Quad, Ghulam Abdul (IIUM Engineering Journal, 2012)
ABSTRACT: This study describes the design of a special type of vertical axis rotor wind turbine with moveable vertically positioned vanes. The novel design increases the torque in the left side of the wind turbine by increasing the drag coefficient. It also reduces the negative torque of the frame which rotates contrary to the wind in the other side. Two different types of models, having different vane shapes (flat vane and cavity shaped vane), were fabricated. Each type consisted of two models with varying number of frames (three and four frames). The models were tested in a wind tunnel with variable wind speed in order to understand the effect of shape, weight, and number of frames on the power coefficient of the wind turbine.Â ABSTRAK: Di dalam kajian ini, rotor turbin angin berpaksi vertikel sebagai rangka khusus telah direkabentuk dengan lokasi vertikel mudahalih oleh bilah kipas. Rekabentuk ini meningkatkan tork di bahagian kiri turbin angin dengan meningkatkan pekali seretan dan mengurangkan tork negatif rangka yang berputar berlawanan dengan angin pada bahagian lain. Dua jenis model berbentuk berlainan telah difabrikasi (bilah kipas rata dan bilah kipas berbentuk kaviti), dengan setiap jenis mempunyai dua model dengan bilangan rangka yang berlainan (berangka tiga dan berangka empat). Model-model telah diuji di dalam terowong angin dengan kelajuan angin yang berbeza bagi mendapatkan kesan rekabentuk, berat dan bilangan rangka ke atas pekali kuasa. KEYWORDS: design; wind turbine; drag coefficient; vane